Feasibility assessment for practical continuous variable quantum key distribution over the satellite‐to‐Earth channel. Issue 3 (23rd August 2020) - Kish, Sebastian P.; Villaseñor, Eduardo; Malaney, Robert; Mudge, Kerry A.; Grant, Kenneth J.
Summary: Currently, quantum key distribution (QKD) using continuous variable (CV) technology has only been demonstrated over short‐range terrestrial links. Here, we attempt to answer whether CV‐QKD over the much longer satellite‐to‐Earth channel is feasible. To this end, we first review the concepts and technologies that will enable CV‐QKD over the satellite‐to‐Earth channels. We then consider, in the infinite key limit, the simplest‐to‐deploy QKD protocols, the coherent state (CS) QKD protocol with homodyne detection and the CS‐QKD protocol with heterodyne detection. We then focus on the CS‐QKD protocol with heterodyne detection in the pragmatic setting of finite keys, where complete security against general attacks is known. We pay particular attention to the relevant noise terms in the satellite‐to‐Earth channel and their impact on the secret key rates. In system set‐ups where diffraction dominates losses, we find that the main components of the total excess noise are the intensity fluctuations due to scintillation, and the time‐of‐arrival fluctuations between signal and local oscillator. We conclude that for a wide range of pragmatic system models, CS‐QKD with information‐theoretic security in the satellite‐to‐Earth channel is feasible.